Detecting Hesperidin in Pharmaceutical Forms via Sensitive and Eco-Friendly Cloud Point Extraction Method Utilizing Spectrophotometry - Salman, Ali Mohammed; Abed, Sadeem Subhi (Indonesian Journal of Chemistry, 2025)
A spectrophotometric method was developed for the determination of hesperidin (HSP) in pharmaceutical preparations and bulk powder, characterized by sensitivity, simplicity, and ecofriendliness. The method involves diazotization of p-chloroaniline (PCA), followed by coupling with HSP in an alkaline medium. The resulting azo product is extracted using the cloud point extraction (CPE) with Triton X-114, and the absorbance was measured at 437 nm. Two approaches were used, i.e., the batch spectrophotometric method and the CPE technique. The batch method showed a detection limit of 0.409 μg/mL, while the CPE method achieved a significantly lower detection limit of 0.023 µg/mL. The linearity ranges were 3–40 and 1–8.5 μg/mL of HSP for the batch and CPE methods. Both methods demonstrated high precision (RSD < 1.17%) and excellent recovery rates, 99.18 to 102.27% for the batch method and 97.32 to 104.28% for CPE, with an enrichment factor of 4.7 using CPE. The methods were successfully applied to the analysis of HSP in supplement formulations and spiked urine samples without significant interference. A greenness evaluation using AGREE software confirmed its environmentally friendly nature. The proposed method offers a reliable, green, low-cost analytical approach suitable for routine pharmaceutical quality control in laboratories to analyze HSP in dosage forms.